PENGARUH ASESMEN DENGAN APLIKASI QUIZIZZ TEHADAP MOTIVASI BELAJAR PESERTA DIDIK SMA YPPK TERUNA BAKTI - Kusa, Aser; Budiarti, Indah Slamet; Boy, Bonefasius Yanwar (Universitas Cenderawasih, 2024)
This study aims to determine the relationship and influence of assessment using the quizizz application on learning motivation. The research method used is quantitative; quasi- experimental one group design, with a questionnaire distribution technique. While the data analysis using descriptive analysis and simple linear regression analysis. Based on the results and data analysis on the linearity and correlation tests, the sig value was obtained. 0.001<0.05 probability value and r count value of 0.704> 0.344 r table, meaning that the two variables have a strong relationship. Based on the t test, it was found that the calculated t value was 5.512> 1.692 t table for 5% of the data for 33 samples or sig. 0.001 <0.05 probability value, meaning that there is influence. So it can be concluded that there is a strong relationship between assessment and APK. quizizz and learning motivation as well as the effect of assessment with the quizizz application on the learning motivation of students at YPPK Teruna Bakti High School with running and stationary wave material with a contribution value of 49.5%. The following linear regression equation is Y = 21.426 + 0.991X.